1988
DOI: 10.1021/bk-1988-0376.ch017
|View full text |Cite
|
Sign up to set email alerts
|

Product Analysis from Direct Liquefaction of Several High-Moisture Biomass Feedstocks

Abstract: Experimental results are reported for high-pressure liquefaction of high-moisture biomass. The feedstocks included macrocystis kelp, water hyacinths, spent grain from a brewery, grain sorghum field residue and napier grass. The biomass was processed in a batch autoclave as a ten weight percent slurry in water with sodium carbonate catalyst and carbon monoxide gas. Thirty-minute experiments were performed at 350°C with operating pressures ranging from 270 to 340 atmospheres. The oil products were collected by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 3 publications
1
39
0
Order By: Relevance
“…By difference, the oxygen content plus all the other traceable compounds in the TCC oils was calculated to be about 12% with a standard deviation of 5%. Experimental results showed that the water content in the raw TCC oils was affected less by the operating parameters, varying from 11.3% to 15.8%.Comparison of the above results to those of typical pyrolysis and liquefied oils is summarized in table 1.The elemental composition of TCC oils was very similar to that of liquefied oil obtained from kelp (Elliott et al, 1988). This means that both processes underwent a similar chemical mechanism except that the liquefied oil from kelp was obtained under much harsher operating conditions and the oil yield was much lower (about 20%) than that in the TCC process (62%-65%).…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…By difference, the oxygen content plus all the other traceable compounds in the TCC oils was calculated to be about 12% with a standard deviation of 5%. Experimental results showed that the water content in the raw TCC oils was affected less by the operating parameters, varying from 11.3% to 15.8%.Comparison of the above results to those of typical pyrolysis and liquefied oils is summarized in table 1.The elemental composition of TCC oils was very similar to that of liquefied oil obtained from kelp (Elliott et al, 1988). This means that both processes underwent a similar chemical mechanism except that the liquefied oil from kelp was obtained under much harsher operating conditions and the oil yield was much lower (about 20%) than that in the TCC process (62%-65%).…”
mentioning
confidence: 65%
“…[c] Summarized from different pyrolysis and liquefaction processes (Rick and Vix, 1991). [d] Extracted from kelp liquefaction product obtained at 350_C and 27.3 to 35.5 MPa, CO initial pressure was 5 MPa (Elliott et al, 1988). [e] n/a = not available.…”
Section: Results and Discussion Elemental Composition And Heating Vamentioning
confidence: 99%
See 3 more Smart Citations